(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
This study aimed to perform morphometric analysis of the mental foramen and mandibular ramus on digital panoramic images and find a highly significant parameter in determining an individual’s sex. A total of 150 digital panoramic images of 75 males and 75 females, aged between 20 and 50 years, were carefully selected based on inclusion criteria from the Dental Screening program data at the Radiology Department of the National Forensic Sciences University in Gujarat. Morphometric analysis of the mental foramen and mandibular ramus was performed, and measurements were taken on the right and left sides of all the O.P.G. images. Measurements of distances from the superior border of the mental foramen to the lower border of the mandible height (SBM-LBM), inferior border of the mental foramen to the lower border of the mandible height (IBM-LBM), condylar height, projective ramus height (P.R.H.) and coronoid height were taken. The obtained data were subjected to statistical analysis, and regression function analysis was used to estimate the efficiency of each variable in sex determination. Our study revealed a highly significant relationship in SBM-LBM, IBM LBM distance, and projective ramus height on both the right and left sides. The left side values were higher than the right side in both males and females. SBM-LBM, IBM-LBM, and ramus height values were higher among males than females. SBM-LBM, IBM-LBM, and projective ramus height showed significant sexual dimorphism.